Conceptualizing leisure within the highly regimented world of elite hockey - MacCosham, B. (Physical Culture and Sport. Studies and Research, 2016)
The purpose of this paper is to offer a conceptualization of leisure that can help us understand what constitutes as leisure and how leisure is attained in a highly regimented context such as elite hockey. Leisure researchers are unable to agree on a definition of leisure that best represents the field, which is perhaps why leisure has lost its significance within contemporary academia. In this paper, a conceptualization is provided that was developed through research on Junior level ice hockey players. Junior level hockey has a highly structured and professionalized regiment but yet, leisure is still attainable for players despite having little control over their involvement. Traditional definitions of leisure do not capture what it means to be in leisure even though theoretically Junior level hockey players are considered to be in serious leisure as amateurs. Thus, this paper can help justify and lets us understand how leisure is attained in Junior level hockey.